Nachbarsprachen und -regionen: Chancen für eine bessere Verständigung in Europa - Bock, Ursula (Glottodidactica, 2000)
The following essay discusses the context of cultural problems and language problems between neighboring countries and regions in Europe. About two thousand years ago Greek and Latin had a lasting influence especially on Western European languages, whereas in the beginning modem era French became the prevailing idiom, which is nowadays removed from English as the language of technology and culture. In addition peoples migrations because of wars and poverty as well as increasing tendencies of globalisation raise the clashes of different languages and cultures all over Europe. Moreover, several European countries, e.g. Belgium, Switzerland or Italy, have to deal with multilingual inhabitants and a lot of cultural and social problems resulting from this situation. The second part of the essay concentrates on the historical and cultural development along the German-Polish borderline during the last 50 years. Special interest lies on the contemporary situation that is marked by increasing cooperation between the two countries. The improvement of cooperation concerns economy as well as culture and science including the promotion of learning the neighboring language on both sides of the frontier and thus building a new region of mutual understanding.